Experimentation made easy with the AMazING panel - Martins, João Marçal (2015)
Experimental testbeds for evaluating solutions in computer networks, are today required as a complement to simulation and emulation. As these testbeds become larger, and accessible to a broader universe of the research community, dedicated management tools become mandatory. These tools ease the complex management of the testbed specific resources, while providing an environment for researchers to define their experiments with large flexibility. While there are currently several management tools, the research community is still lacking tools that smooth the experimentation workflow. These were key aspects that we considered when developing the management infrastructure for our wireless testbed[4] (AMazING). We developed a experimentation support framework supported by an attractive GUI, automation and scripting capabilities, as well as experiment versioning and integrated result gathering and analysis.